What is Known About Environmental Cost Accounting? Systematic Literature Review - Citra Dhistia Murti (Journal of Accounting and Investment, 2023)
Research aims: This study evaluates articles dealing with environmental cost accounting to learn a valuable lesson. Design/Methodology/Approach: This study used the review procedure by Hoque (2014) with several analyzes employed in the prior research by Anggraini et al. (2022). Articles were then reviewed and identified by entering the keywords "environmental" AND "cost" AND "accounting" in the Scopus database. After applying several criteria, this study utilized 45 articles for further analysis.Research findings: Four discussion themes can be further identified. The four topics discussed in this article included environmental cost accounting measurement, implementation, environmental performance, and environmental cost accounting disclosures.Theoretical contribution/Originality: Given the importance of environmental cost accounting applied in companies, to the best of the author's knowledge, there has been no literature review research on environmental cost accounting. Furthermore, this research explains what lessons can be drawn.